2018
DOI: 10.1128/aem.02107-17
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of Early Bacterial Biofilms on Different Wood Typologies Applied in Dairy Production

Abstract: The main hypothesis of this work was that Sicilian forestry resources are suitable for the production of equipment to be used in cheese making and indigenous milk lactic acid bacteria (LAB) are able to develop stable biofilms providing starter and nonstarter cultures necessary for curd fermentation and cheese ripening, respectively. Hence, the present work was carried out with deproteinized whey to evaluate LAB biofilm formation on different woods derived from tree species grown in Sicily. Microbiological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 38 publications
3
48
0
Order By: Relevance
“…Several previous studies have focused on naturally fermented foods, including artisanal cheeses (46), Chinese liquor (47), and dairy products (4849). In addition, there has been some research into the microbial diversity of shrimp culture environments, and the chemical composition and sensory attributes of shrimp paste [50].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have focused on naturally fermented foods, including artisanal cheeses (46), Chinese liquor (47), and dairy products (4849). In addition, there has been some research into the microbial diversity of shrimp culture environments, and the chemical composition and sensory attributes of shrimp paste [50].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study no inhibitory compounds by biofilm microflora were observed [49]. Therefore this reduction in L. monocytogenes numbers can be attributed to "Jameson effect" according to the nutrient consumption and exhaustion by competitive microorganisms [49] [60] [61]. This type of effect can be used on wood for treatment with probiotic type microorganisms and their bio-surfactants, which may antagonize the growth of nosocomial pathogens on inanimate surfaces [62].…”
Section: Microbial Adherence and Biofilm Formation On Wood Surfacementioning
confidence: 92%
“…Mariani et al [59] (CFU/cm 2 ) when the resident biofilm was thermally inactivated, suggesting a microbial origin of the observed inhibitory effect. In a similar study no inhibitory compounds by biofilm microflora were observed [49]. Therefore this reduction in L. monocytogenes numbers can be attributed to "Jameson effect" according to the nutrient consumption and exhaustion by competitive microorganisms [49] [60] [61].…”
Section: Microbial Adherence and Biofilm Formation On Wood Surfacementioning
confidence: 95%
See 1 more Smart Citation
“…Different microbial groups were investigated as follows: total mesophilic microorganisms (TMM) and total psychrotrophic microorganisms (TPM) on plate count agar PCA; pseudomonads on Pseudomonas agar base (PAB) added with CFC supplement; members of the Enterobacteriaceae family on double-layered violet red bile glucose agar (VRBGA); total coliforms on double-layered violet red bile agar (VRBA); enterococci on kanamycin aesculin azide (KAA) agar; coagulase-positive and coagulase-negative staphylococci (CPS and CNS) on Baird Parker (BP) added with RPF supplement; L. monocytogenes on Listeria selective agar base (LSAB) added with SR0140E supplement; yeasts on yeast extract peptone dextrose (YPD) agar supplemented with 0.1 g/L chloramphenicol to avoid bacterial growth. The incubation conditions are described in Cruciata et al (2018). All media and supplements were purchased from Oxoid (Milan, Italy).…”
Section: Microbiological Analyses and Isolation Of The Dominant Micromentioning
confidence: 99%